Atomistic simulation of < c + a > screw dislocation cross-slip in Mg. (May 2016) - Buey, D.; Ghazisaeidi, M.
Abstract: The core structure and glide behavior of a 〈 c  +  a 〉 screw dislocation in Mg is studied using molecular dynamics simulations at 0 K, 70 K and 300 K. We find that slip on pyramidal II planes is preferred at 300 K. At lower temperatures, the dislocation cross slips between pyramidal II and pyramidal I planes with sufficient applied stress. We find a metastable compact core structure, with an intermediate core energy between those of the dissociated dislocations on pyramidal II and pyramidal I planes. This compact core is observed in the cross slip from pyramidal II to pyramidal I planes at 0 K and 70 K. Graphical abstract: